2016
DOI: 10.1007/s11665-016-2003-x
|View full text |Cite
|
Sign up to set email alerts
|

High-Temperature Interaction Between Molten AlSr10 Alloy and Glass-Like Carbon Substrate

Abstract: Wettability of glass-like carbon substrate (C glc ) by molten Al-10 wt.% Sr alloy (AlSr10) has been examined by a sessile drop method at 700-800°C for 120 min under vacuum. Non-contact heating to the test temperature combined with the removal of oxide film from the alloy drop was done using capillary purification procedure by squeezing the liquid alloy from a capillary. The influence of the type of capillary on wetting behavior of AlSr10/C glc couples was noticed. Molten AlSr10 alloy does not wet C glc at abou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…In all the former studies [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ], no significant work was performed on studying the wetting behavior of liquid Al-Si-Cu alloy in contact with Al dross substrate with particular emphasis on the CP procedure. Hence, the novelty of the present study is first providing wettability information of Al-Si-Cu/Al dross systems, secondly the application of the CP procedure in the Al dross wettability test, and third providing microstructural information of Al-Si-Cu/Al dross systems.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In all the former studies [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ], no significant work was performed on studying the wetting behavior of liquid Al-Si-Cu alloy in contact with Al dross substrate with particular emphasis on the CP procedure. Hence, the novelty of the present study is first providing wettability information of Al-Si-Cu/Al dross systems, secondly the application of the CP procedure in the Al dross wettability test, and third providing microstructural information of Al-Si-Cu/Al dross systems.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, the novelty of the present study is first providing wettability information of Al-Si-Cu/Al dross systems, secondly the application of the CP procedure in the Al dross wettability test, and third providing microstructural information of Al-Si-Cu/Al dross systems. Literature survey [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ] revealed that available papers are mostly concerned with the study of the wettability of pure Al [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ] and its alloys [ 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ] in contact with various types of substrates, such as Al 2 O 3 [ 29 , 34 ], TiO 2 [ 30 , 34 ], C [ 31 , 38 , 40 , 44 ], NiO [ 32 ], SiC [ 33 , 39 ], ZrO 2 [ <...>…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The problems of molten zones formation and their subsequent migration over material surface are of interest from the viewpoint of both developing novel technological methods of forming microelectronic structures (Anson et al, 1999;Mills and Su, 2006;Siewiorek et al, 2016;Lischner et al, 2016;Liu et al, 2017;Eisaabadi and Nouri, 2018) and application of such drops as primary working elements of microlenses and reflectors (Shi, 2008;Wang et al, 2011;Zohrabi et al, 2016;He et al, 2019), displays, weighers (Zhongping et al, 1995 Skvortsov et al, 2017). Such processes start to appear at the local rise of temperature produced by high current densities j = 10 9 -10 10 А/m 2 .…”
Section: Introductionmentioning
confidence: 99%